Early detection of autism spectrum disorder in young isiZulu-speaking children in South Africa. (July 2017) - Chambers, Nola J; Wetherby, Amy M; Stronach, Sheri T; Njongwe, Nonyameko; Kauchali, Shuaib; Grinker, Richard R
Culturally appropriate tools are needed for detecting symptoms of autism spectrum disorder in young South African children. The objectives of this study were to (1) adapt and translate into isiZulu existing measures for detecting early signs of autism spectrum disorder, (2) use the measures to characterize and compare behavioural profiles of young isiZulu-speaking children with and without autism spectrum disorder and (3) compare symptom profiles across sampling procedures. Measures were translated and adapted into isiZulu and used to evaluate 26 isiZulu-speaking children, 15 children with no reported developmental concerns and 11 referred for suspected autism spectrum disorder. A video-recorded observation of children and caregivers in their home environment was also made. Based on best-estimate diagnoses, 10 children were classified as autism spectrum disorder and 16 as non-autism spectrum disorder. The children with autism spectrum disorder presented with significantly more autism spectrum disorder red flags than the non-autism spectrum disorder group according to parent report and systematic ratings of red flags. Significant correlations between parent report and observational measures of red flags were observed. More red flags were observed during structured evaluations than home observations in the autism spectrum disorder group. Findings provide a foundation for tool translation and adaptation in South Africa and identifying social communication markers to detect autism spectrum disorder in young isiZulu-speaking children.